2015
DOI: 10.1002/mnfr.201500466
|View full text |Cite
|
Sign up to set email alerts
|

ERK5/HDAC5‐mediated, resveratrol‐, and pterostilbene‐induced expression of MnSOD in human endothelial cells

Abstract: Resveratrol and pterostilbene, present in fruits, red wine and some Chinese medicine herbs, activate MnSOD expression, and stimulate LKB1, AMPK, ERK5 phosphorylation and HDAC5 and KLF2 expression in endothelial cells. Furthermore, two stilbenes promote KLF2 binding to human MnSOD promoter. These findings reveal a new mechanism underlying the anti-aging effect two stilbenes exert on vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, Compound C, a potent selective and reversible AMP-kinase inhibitor, inhibited EPC differentiation stimulated by BavaC, and the percentage of CD31 + /CD34 + cells was only 0.25 ± 0.03% (n = 3, P < 0.05; Figure 5C and 5D ), suggesting that BavaC-induced AMPK activity is related to the differentiation of endothelial cells. Considering our previous finding that extracellular signal-regulated kinase 5 (ERK5) is the downstream signal molecule of AMPK [ 35 ], we evaluated the effect of ERK5 on EPC differentiation. The results showed that XMD8-92 at a final concentration of 5 μM, an inhibitor of ERK5, reversed BavaC-induced EPC differentiation, and the proportion of the cells decreased from 2.08 ± 0.11% to 1.57 ± 0.07%, which was similar to the 1.61 ± 0.04% of the control (n = 3, P < 0.05; Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Compound C, a potent selective and reversible AMP-kinase inhibitor, inhibited EPC differentiation stimulated by BavaC, and the percentage of CD31 + /CD34 + cells was only 0.25 ± 0.03% (n = 3, P < 0.05; Figure 5C and 5D ), suggesting that BavaC-induced AMPK activity is related to the differentiation of endothelial cells. Considering our previous finding that extracellular signal-regulated kinase 5 (ERK5) is the downstream signal molecule of AMPK [ 35 ], we evaluated the effect of ERK5 on EPC differentiation. The results showed that XMD8-92 at a final concentration of 5 μM, an inhibitor of ERK5, reversed BavaC-induced EPC differentiation, and the proportion of the cells decreased from 2.08 ± 0.11% to 1.57 ± 0.07%, which was similar to the 1.61 ± 0.04% of the control (n = 3, P < 0.05; Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that XMD8-92, an inhibitor of ERK5, inhibited EPC differentiation, as revealed by flow cytometry (Figure 5E ). Our previous results showed that resveratrol and pterostilbene stimulated AMPKα and ERK5 activity, and expression of MnSOD and KLF2, as well as reduce mitochondrial superoxide radical and endothelial cell senescence [ 35 ]. Prior studies have shown that ERK5 is an upstream signal molecule for KLF2 expression [ 35 , 47 ], and a transcription factor that regulates eNOS and MnSOD expression [ 46 , 48 ] and promotes EPC differentiation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the protein abundance and activity of serine/threonine kinase 11, an upstream signaling molecule for AMPK, have been found to be similar in both aerobic and ischemic hearts [ 25 ]. Previous studies of our and other groups have demonstrated that ingredients in Chinese medical herbs, such as 2,3,5,4′-tetrahydroxystilbene-2-O- β -D-glucoside, bavachalcone, diosgenin, and pterostilbene, stimulated the AMPK activity and anti-inflammatory effects [ 17 , 50 55 ]. To date, some studies have demonstrated that the activation of AMPK inhibits NLRP3 expression, caspase-1 activity, and IL-1 β secretion [ 56 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of band density was performed using Quantity One software from Bio-Rad (Hercules, CA, USA). Western blot experiments were performed in triplicate [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…RVT also attenuated mtROS-mediated oxidative injury in human umbilical vein endothelial cells (HUVECs) via SIRT3 activation [ 133 ]. Xu and coworkers showed that the upregulation of Mn-SOD occurs via the extracellular-signal related kinase 5 (ERK5)/HDAC5 pathway, which then reduces mtROS levels in HUVECs [ 134 ].…”
Section: Histone Deacetylasementioning
confidence: 99%